SE4RL: piloting alternative models of solarization - Kuriachen, Philip (International Water Management Institute, 2024)
Solar energy for rural livelihoods has pilot tested solar irrigation enterprises as an alternative pathway for agriculture solarization. The project has field tested three models in Bihar, Eastern UP and Jharkhand which were tailored to local socio-ecological and agrarian conditions. Solar irrigation as a micro-enterprise was tested in Bihar with the objective of catalysing buyer friendly water markets. Solar irrigation enterprises have generated approximately cumulative revenue of 0.5 million rupees while reducing irrigation expenditure of water buyers by 80,000 rupees. In Jharkhand, to address the unique challenges of inadequate access to affordable power limiting irrigation and subsequently agriculture expansion, we pilot tested the feasibility of Farmer producer companies as irrigation service providers. The FPC model has shown better performance on key parameters like irrigation coverage and capacity utilization vis-à-vis PM-KUSUM and community lift irrigation schemes under JOHAR. In UP, working with Oorja SE4RL field tested the sensitivity of irrigation service fee on capacity utilization and revenues from irrigation sales. The field experiment reduced irrigation fee from Rs 4 to Rs 2 per cubic metre leading to a 7% increase in revenue and doubling of irrigation sales for Oorja. The pilots indicate that solar irrigation enterprises are a viable alternative to conventional strategy of promoting individual SIPs with large capital subsidies.